Evaluation of elabela, apelin and nitric oxide findings in maternal blood of normal pregnant women, pregnant women with pre-eclampsia, severe pre-eclampsia and umbilical arteries and venules of newborns - Deniz, Rulin; Baykus, Yakup; Ustebay, Sefer; Ugur, Kader; Yavuzkir, Seyda; Aydin, Suleyman (Taylor & Francis Inc, 2019)
Pre-eclampsia is multisystem metabolic diseases, commonly accompanied by hypertension and proteinuria, which are among the important causes of maternal and perinatal mortality and morbidity worldwide. In a pre-eclampsia animal model study in the last year, Elabela (ELA) infusion was reported to correct hypertension and proteinuria and to normalise the birth weights of the offspring. Therefore, our main goal in this human study is to compare ELA, apelin (APLN) and nitric oxide (NO) levels in the maternal blood of pregnant women with pre-eclampsia and severe pre-eclampsia and in their newborns' venous-arterial cord blood with maternal blood of healthy pregnant women and their newborns' venous-arterial cord blood. Thirty controls, 28 pre-eclampsia and 24 severe pre-eclampsia cases and their newborns participated in this study. Maternal blood and newborn venous-arterial cord blood samples were collected from these patients. ELA, APLN and NO levels in these samples were measured by ELISA method. When the maternal blood ELA, APLN and NO amounts were compared with control groups, there was a significant decrease in both pre-eclamptic and severe pre-eclamptic women and this was more prominent in the women with severe pre-eclampsia. When ELA, APLN and NO levels in the newborn venous-arterial cord blood of control group was compared with that of severe pre-eclamptic and pre-eclamptic women; it was parallel with maternal findings. ELA, APLN and NO levels appear to play a role in the pathophysiology of pre-eclampsia. It is predicted that if these molecules, which are reduced due to pre-eclampsia and severe pre-eclampsia, are brought to physiological limits in the future; pre-eclampsia related maternal and perinatal mortality and morbidity can be reduced.Impact Statement What is already known on this subject? There are two studies (one human and one animal) in the literature evaluating only maternal elabela (ELA) levels in pre-eclamptic pregnancies. The animal study demonstrated decreased blood ELA levels in pre-eclamptic animals and the human study found increased blood ELA levels in pre-eclamptic patients. There are no studies evaluating maternal ELA levels in severe pre-eclampsia patients and also there are no studies evaluating maternal ELA levels in pre-eclampsia and severe pre-eclampsia patients. There are no studies evaluating newborns' venous-arterial blood APLN and NO levels. Apelin (APLN) and nitric oxide (NO) results were controversial in pre-eclampsia and severe pre-eclampsia patients. What the results of this study add? The present study, for the first time, demonstrates that decreased blood ELA, APLN and NO levels in maternal blood of pregnant women with pre-eclampsia and severe pre-eclampsia and in their newborns' venous-arterial blood. Furthermore, we have also demonstrated for the first time that decreased ELA, APLN and NO are also related with low birth weights. What are of these findings for clinical practice and/or further research? The low levels of ELA, APLN and NO in maternal blood and newborns' venous-arterial blood may be the result or the cause of pathologic changes in pre-eclampsia and severe pre-eclampsia. Also, ELA, APLN and NO may be new indicator parameters of systemic endothelial dysfunction together. More studies are needed to evaluate the relationship between of ELA, APLN and NO and pre-eclampsia and severe pre-eclampsia and in newborns' venous-arterial blood.
Keywords: Elabela; severe pre-eclampsia; nitric oxide; apelin; umbilical artery; venules